KAJIAN PERBANDINGAN KURIKULUM PENDIDIKAN VOKASI TEKNIK MESIN UNTUK MENJAWAB TANTANGAN PADA ERA 4.0 DI TANAH PAPUA - Sigit Hernowo; Nelce D. Muskita; Surianto Buyung; Yolanda J. Lewerissa (LPPM Politeknik Saint Paul Sorong, 2026)
The development of technology in the Industrial Revolution 4.0 era requires vocational higher education institutions to produce graduates who possess technical competencies, technological adaptability, and work readiness that meet the needs of industry and business sectors. This study aims to conduct a comparative analysis of Mechanical Engineering curricula in Indonesia as a basis for developing the Applied Bachelor's Degree Curriculum in Mechanical Engineering at Saint Paul Polytechnic Sorong. The research employed a descriptive-comparative approach using document analysis methods on five Mechanical Engineering study programs that have implemented Outcome-Based Education (OBE), consisting of three academic programs and two vocational programs. Data were collected through documentation studies of graduate profiles, learning outcomes, curriculum structures, and supporting curriculum documents. Data analysis was conducted using content analysis and comparative analysis to identify similarities, differences, and unique characteristics among the curricula. The results indicate that all study programs have implemented OBE principles aligned with the National Standards of Higher Education (SN-Dikti), the Indonesian National Qualification Framework (KKNI), and the Merdeka Belajar Kampus Merdeka (MBKM) policy. Academic programs tend to emphasize analytical and engineering development competencies, while vocational programs focus more on applied competencies and industrial needs. Common characteristics were found in the mastery of engineering sciences, design capabilities, engineering problem-solving skills, professional communication, and lifelong learning competencies. The findings of this study can serve as a reference for developing a curriculum that is relevant to industrial needs and the regional development characteristics of Papua.